Application of international energy efficiency standards for energy auditing in a University buildings - V. Shcherbak; L. Ganushchak-Yefimenko; O. Nifatova; P. Dudko; N. Savchuk; I. Solonenchuk (Global Journal of Environmental Science and Management)
This study seeks to provide insights on understanding the contemporary problems of energy efficiency in Ukrainian universities by developing a comprehensive energy efficiency management framework that encompasses its participating subjects, objects and key drivers along with suggesting its implementation mechanism and tools. Emphasis should be given that the current situation of inefficient and irrational consumption of energy resources within the system of higher education in Ukraine challenges the development of an integrative approach to energy saving and energy efficiency management. It is argued that the key elements of this integrative approach to energy management are energy auditing, energy certification and energy monitoring based on the consistent use of ISO 9000 international standards. Over the last 10 years energy consumption in Ukrainian higher education institutions against the world best practice exceed by 30-40%. This triggers a critical need to building an integrative approach to energy saving and energy efficiency management. The findings revealed that disincentives reduce the degree of energy efficiency by 25%. Constructing energy profiles by a hierarchical clustering method demonstrated that 68% of the campus buildings belong to a 5th class out of 7, i. e. being highly energy intensive. Following the DGNB (German Sustainable Building Council) approach to evaluate energy efficiency has enabled to eliminate 17% of the G category classrooms (extra energy intensive) from the University heating facilities. The clustering method to assess 15 University buildings by 16 performance indicators identified 5 clusters in terms of energy consumption and energy efficiency.